OPTIMALISASI SAMPAH BERBASIS PEMBERDAYAAN MASYARAKAT DAN PENGUATAN MODERASI BERAGAMA DI KELURAHAN CISANTANA - Nuryadin, Nuryadin; Karim, Ahmad Zafirul; Lestari, Andry; Husna, Kania; Zulfaidah, Rena (Sekolah Tinggi Agama Islam Negeri Majene, 2024)
Cisantana Village, with its rich local wisdom and natural resource potential, has significant opportunities to manage waste effectively. The challenges in this village, as in other places, involve increasing waste volumes due to population growth and rapid economic activities. An approach that involves community empowerment and the integration of religious moderation can provide an effective solution. Community empowerment through programs like waste banks, which emphasize the 3R principles (Reduce, Reuse, Recycle), can raise awareness and encourage public participation. Furthermore, the strong religious moderation in Cisantana Village can serve as a foundation for fostering cooperation across different community groups in waste management, instilling values of tolerance, balance, and mutual respect. The Community-Based Empowerment System (SISDAMAS) method applied in this effort positions the community as key agents in problem-solving. Through program implementation that involves field observations, community involvement in finding solutions, as well as monitoring and evaluation, the waste bank program is expected to positively impact both the economy and social harmony. The integration of community empowerment and religious moderation also faces challenges, such as differences in religious understanding and practices, limited facilities, and resources. However, with a collaborative approach involving the government, private sector, and civil society organizations, these challenges can be managed. In this way, Cisantana Village can develop a more effective, inclusive, and sustainable waste management system.